2009
DOI: 10.1017/s1049096509090064
|View full text |Cite
|
Sign up to set email alerts
|

Meaningful Participation and the Evolution of the Reformed Presidential Nominating System

Abstract: F orty years ago, violent protests at the Democratic National Convention captured the attention of the nation as rioters vented their anger over a nomination process they felt excluded their voices. The disastrous 1968 convention spawned a cascade of reforms in the presidential nomination system, many of which were intended to create greater opportunity for meaningful participation of the party's rank-and-file members. Forty years later, where do we stand? Does the nomination process meet the goals of encourag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…However, this party divisiveness clearly did not determine the winner in November, as was suggested by the earlier findings of Atkeson (1998), Southwell (1986; 1994), and Ware (1979). Some scholars have suggested that such competitive races may actually help the party in the long run, because they help to mobilize young, less-educated, and low-income voters (Atkeson and Maestas 2009) or party activists (Stone, Atkeson, and Rapoport 1992). From the standpoint of the two major parties, multicandidate races for the nomination may be less than desirable for the party, but the 2008 general election results suggest that this occurrence is an obstacle that can be overcome.…”
Section: Discussionmentioning
confidence: 99%
“…However, this party divisiveness clearly did not determine the winner in November, as was suggested by the earlier findings of Atkeson (1998), Southwell (1986; 1994), and Ware (1979). Some scholars have suggested that such competitive races may actually help the party in the long run, because they help to mobilize young, less-educated, and low-income voters (Atkeson and Maestas 2009) or party activists (Stone, Atkeson, and Rapoport 1992). From the standpoint of the two major parties, multicandidate races for the nomination may be less than desirable for the party, but the 2008 general election results suggest that this occurrence is an obstacle that can be overcome.…”
Section: Discussionmentioning
confidence: 99%
“…The 2008 presidential nomination contests were the most competitive in modern history, with the Democratic battle lasting into June with record turnout in primaries and caucuses across the nation. Normally turnout in presidential primaries slowly decreases over time as the field of candidates is winnowed and a clear winner emerges (Atkeson and Maestas 2009 in this symposium). Compared to 30% turnout in 2004, turnout in the 2008 New Hampshire primary was over 50% of the voting eligible population (VEP), a 20-point increase.…”
Section: Back To the Drawing Board: The Broken Presidential Nominatiomentioning
confidence: 96%
“…The highly competitive Democratic Party nomination was driven after Super Tuesday by the battle between Barack Obama and Hillary Clinton. Some argue competition in general is a good thing (Donovan 2007; Atkeson and Maestas 2009 in this symposium) and not only increases turnout (Cox and Munger 1989) but can alter the composition of the electorate, reducing bias (Donovan and Tolbert 2007). Others suggest competition fosters party building activities (Stone, Atkeson, and Rapoport 1992).…”
Section: Back To the Drawing Board: The Broken Presidential Nominatiomentioning
confidence: 97%
See 1 more Smart Citation
“…The current system was first implemented in 1972 when new party rules, among other things, connected outcomes at first tier selection events such as caucuses or primaries to candidate delegate counts and ensured that partisans wanting to participate had access to the selection process (Mandate for Reform 1970). This led to greater participation of rank-and-file party members and more internal party democracy in selecting the party nominee, in part, because many states moved from a caucus to a primary to satisfy the new rules resulting in grater turnout (Atkeson and Maestas 2009). However, the sequential nature of the presidential nomination process encourages or discourages primary participation depending on the dynamics of the race.…”
mentioning
confidence: 99%